2018
DOI: 10.1155/2018/2746347
|View full text |Cite
|
Sign up to set email alerts
|

11p15.4 Microdeletion Associates with Hemihypertrophy

Abstract: We report a preterm female infant with intrauterine growth retardation, dysmorphic facies, missing rib, small hands and feet, and hemihypertrophy. The results of whole genome SNP microarray analysis showed approximately 77 Kb interstitial deletion of the short arm of chromosome 11 (11p15.4). We report novel clinical findings of this rare genetic condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A genetic evaluation revealed that confirmation of NPD type A was provided by a twofold change in the sequence encoding the SMPD1 gene, which was found on chromosome 11p15.4. The association between 11p15.4 microdeletion and hemihypertrophy was presented in a case reported by Puvabanditsin et al [ 11 ] that explains the associated neurological deficits among NPD cases. Later, the current case showed signs of respiratory infection.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic evaluation revealed that confirmation of NPD type A was provided by a twofold change in the sequence encoding the SMPD1 gene, which was found on chromosome 11p15.4. The association between 11p15.4 microdeletion and hemihypertrophy was presented in a case reported by Puvabanditsin et al [ 11 ] that explains the associated neurological deficits among NPD cases. Later, the current case showed signs of respiratory infection.…”
Section: Discussionmentioning
confidence: 99%